Emergence of Macrolide-Resistant Mycoplasma pneumoniae in Hong Kong Is Linked to Increasing Macrolide Resistance in Multilocus Variable-Number Tandem-Repeat Analysis Type 4-5-7-2 - Ho, Pak-Leung (J Clin Microbiol, 2015)
Macrolide-resistant Mycoplasma pneumoniae (MRMP) is rapidly emerging in Asia, but information on the temporal relationship between the increase in macrolide resistance and changes in strain types is scarce. Between 2011 and 2014, M. pneumoniae infection was diagnosed by PCR as part of routine care in a health care region in Hong Kong. Testing was initiated by clinicians, mainly in patients with suspected M. pneumoniae pneumonia. Specimens positive for M. pneumoniae were retrospectively investigated by macrolide resistance genotyping and a four-locus (Mpn13 to -16) multilocus variable-number tandem-repeat analysis (MLVA) scheme. The overall percentage of M. pneumoniae-positive specimens was 17.9%, with annual rates ranging from 9.8% to 27.2%. The prevalence of MRMP had rapidly increased from 13.6% in 2011 to 30.7% in 2012, 36.6% in 2013, and 47.1% in 2014 (P = 0.038). Two major MLVA types, 4-5-7-2 and 3-5-6-2, accounted for 75% to 85% of the infections each year. MLVA types 4-5-7-2 and 3-5-6-2 predominated among macrolide-resistant and macrolide-sensitive groups, respectively. The increase in MRMP was mainly caused by increasing macrolide resistance in the prevalent MLVA type 4-5-7-2, changing from 25.0% in 2011 to 59.1% in 2012, to 89.7% in 2013, and to 100% in 2014 (P < 0.001). In conclusion, increasing MRMP in Hong Kong was linked to a single MLVA type, which was both prevalent and increasingly resistant to macrolides.